The effect of learning culture on self-efficacy of special intelligent students in senior high school - Ananda Aprilia; Siti Masyithoh; Mu’arif SAM (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2021)
Special intelligent students are excellent human resources and are expected to make a major contribution to people's lives, including achievement in the academic field. With this extraordinary intelligence, special intelligent students should have high self-efficacy, but they are often found who are not confident in their abilities and have an impact on the learning achievement that is not optimal. This is because there are still some of them who do not have a good learning culture. This study aims to analyze the contribution of learning culture to the self-efficacy on special intelligent students in senior high school. This research was used a quantitative method with sampling based on the simple random sampling technique developed by Isaac and Michael. Data were collected using questionnaires, interviews, and documentation studies. Based on SPSS Ver.22 data processing, the results of the correlation test (r-test) show that there is a significant correlation between learning culture and self-efficacy of special intelligent students in a very strong and unidirectional level. The result shows that learning culture has a positive effect on the self-efficacy of special intelligent students. In the calculation of the coefficient of determination, it is known that the effect of learning culture on the self-efficacy of special intelligent students is 68.6%, while the remaining 31.4% is influenced by other factors not examined. It can be concluded that learning culture has a positive effect on the self-efficacy of special intelligent students. The better learning culture of special intelligent students, the higher their self-efficacy.